The association between nutritional assessment tools and CT-assessed sarcopenia in abdominal aortic aneurysm: a cross-sectional study - Yao, Jiashu; Zhang, Yepeng; Chen, Wenqing; Li, Xiangrui; Wu, Guangyan; Wang, Jie; Chen, Xiaotian; Gao, Bo; Zhou, Min (Frontiers in Nutrition, 2025)
ObjectiveTo evaluate the correlation between computed tomography (CT)-assessed sarcopenia and nutritional assessment tools in patients with abdominal aortic aneurysm (AAA).MethodsIn this single-center retrospective study, 232 AAA patients admitted to our hospital between January 2022 and December 2024 were included. Patients’ demographic characteristic were collected. Nutritional assessment tools were calculated, including the nutritional risk screening 2002 (NRS2002), controlling nutritional status (CONUT) score, geriatric nutritional risk index (GNRI), and prognostic nutritional index (PNI). Sarcopenia was diagnosed through CT measured skeletal muscle mass index at the third lumbar vertebra level, including rectus abdominis, internal/external obliques, transversus abdominis, erector spinae, quadratus lumborum, and psoas muscles. Logistic regression analysis was used to assess the association between nutritional assessment tools and sarcopenia in AAA patients. The optimal cutoff values of each nutritional assessment tools for screening sarcopenia in AAA patients were determined based on receiver operating characteristic (ROC) curve analysis.ResultsMultivariate regression analysis revealed that NRS2002 (odds ratio [OR] 1.83, 95% confidence interval [CI] 1.27 ~ 2.63), CONUT (OR 1.40, 95% CI 1.18 ~ 1.66), and GNRI (OR 0.90, 95% CI 0.85 ~ 0.95) were independently associated with sarcopenia in AAA patients (p < 0.05). NRS2002 (AUC = 0.735) outperformed CONUT (AUC = 0.613) and PNI (AUC = 0.600) in sarcopenia screening, showing comparable accuracy to GNRI (AUC = 0.694), with superior specificity (92.11% vs. 57.89%) but lower sensitivity (48.45% vs. 78.76%) than GNRI.ConclusionNRS2002 and GNRI demonstrated potential as supportive assessment methods. Their clinical utility as independent screening tools in sarcopenia among AAA patients remained limited due to their respective low sensitivity/specificity.